Experimental Investigations of Cement Clay Interlocking Brick Masonry Structures Strengthened with CFRP and Cement-Sand Mortar - Joyklad, Panuwat; Waqas, Hafiz Ahmad; Hafeez, Abdul; Ali, Nazam; Ejaz, Ali; Hussain, Qudeer; Khan, Kaffayatullah; Sangthongtong, Arissaman; Saingam, Panumas (My University, 2023)
Many masonry structures are constructed with cement clay interlocking brick (CCIB) due to its added benefits. Recent research has demonstrated the vulnerability of brick masonry walls against seismic loading. Various strengthening materials and techniques are extensively used to improve the structural behavior of brick walls. Carbon fiber-reinforced polymer (CFRP) composites are the most popular strengthening material due to their advantages of easy application, lightweight qualities, and superior tensile strength. The current research work aimed to explore the cost-effective solutions and feasibility of CFRP composite-based strengthening techniques to improve the load-bearing capacity of CCIB walls. Various configurations and combinations of strengthening materials were investigated to customize the cost of repair and strengthening. The experimental results indicated that CFRP composites in combination with cement-sand (CS) mortar are an efficient strengthening material to enhance the strength and ultimate deflection of CCIB walls. The ultimate load-bearing capacity and axial deformation of the strengthened CCIB wall (using two layers of CFRP strips and CS mortar of 10 mm thickness) remained 171% and 190% larger than the unstrengthened CCIB wall. The conclusions of this study are expected to enhance the seismic performance of masonry buildings in developing countries. It should be noted that due to the reduced number of tested specimens, the results to be assumed as general considerations need a wider experimental campaign and a large numbers of tests for each strengthening typology.
Keywords: axial capacity; bricks; cement; CFRP; clay; masonry walls; mortar; strengthening